Préparer l’inattendu - Célia De Pietro (Revue d'anthropologie des connaissances)
In the media, militant actions are often described as unexpected appearances in the public space. Yet these demonstrations are the fruit of long hours of preparation. This article explores this often overlooked preparatory phase, focusing on the Extinction Rebellion (XR) movement. Based on an ethnographic immersion in a Swiss-based group since 2019, this article presents two cases that examine the preparation of an action from the point of view of a person taking part in it without coordinating it. The first example shows how XR rebels learn to react to the unexpected by acquiring knowledge and skills and drawing on their past experiences. The second case study focuses on an action situation where everything goes according to plan, highlighting how the rebels still must reconcile the absence of certain information inherent in carrying out illegal actions, which gives them a feeling of doubt, with the trust they need to place in the group coordinating the action to continue acting.